Ofatumumab monotherapy as a consolidation strategy in patients with previously untreated chronic lymphocytic leukaemia: a phase 2 trial. Issue 9 (September 2016) - Strati, Paolo; Lanasa, Mark; Call, Timothy G; Leis, Jose F; Brander, Danielle M; LaPlant, Betsy R; Pettinger, Adam M; Ding, Wei; Parikh, Sameer A; Hanson, Curtis A; Chanan-Khan, Asher A; Bowen, Deborah A; et al.
Summary: Background: Although several consolidation strategies to prolong treatment-free survival (TFS) in chronic lymphocytic leukaemia have been investigated, most have proven either ineffective or toxic. Ofatumumab is a human type I anti-CD20 antibody approved by the US Food and Drug Administration as maintenance treatment of patients with recurrent or progressive chronic lymphocytic leukaemia who are in complete or partial response after at least two lines of treatment; higher efficacy might be observed if used as consolidation strategy than without consolidation in previously untreated patients. Methods: We recruited patients with previously untreated progressive chronic lymphocytic leukaemia who had an Eastern Cooperative Oncology Group performance status of 0–2 and adequate renal and hepatic function from centres in the USA. Patients with recent myocardial infarction; class III or IV heart failure; uncontrolled, HIV, or active hepatitis B or C infection; or active haemolytic anaemia were excluded. In the first arm of this study, which has been previously reported, patients were treated with six cycles of induction with pentostatin (2 mg/m 2 on day 1), cyclophosphamide (600 mg/m 2 on day 1), and ofatumumab (cycle 1: 300 mg on day 1 and 1000 mg/m 2 on day 2; cycles 2–6: 1000 mg/m 2 on day 1) given intravenously every 21 days. Here were report the second arm, where patients received the same regimen as the first arm, with the addition of six cycles of consolidation with ofatumumab (1000 mg once every 4 weeks), also given intravenously. The primary endpoint was TFS at 18 months, assessed in those who began consolidation. We estimated the distribution of TFS using the Kaplan-Meier method, assessing between-group differences with log-rank statistics. The phase 2 trial, which is completed, is registered atClinicalTrials.gov, numberNCT01024010 . Findings: Between Sept 21, 2011, and Nov 7, 2012, 34 patients were recruited to this second arm of the trial. Among the 31 (91%) patients who completed induction treatment and started consolidation, 26 (84%) completed the planned six cycles of ofatumumab consolidation. TFS at 18 months was 94·1% (95% CI 78·5–98·5). Grade 3 or worse adverse events deemed at least possibly related to treatment were neutropenia (14 [41%] patients), infection (2 [6%]), and one (3%) each with anaemia, haemolysis, fatigue, and a neurological, metabolic, respiratory, and vascular complication. Interpretation: Ofatumumab-based consolidation appears to be a well tolerated and effective consolidation strategy in patients with chronic lymphocytic leukaemia, which could improve survival. Funding: GlaxoSmithKline.